2014
DOI: 10.1093/mnras/stu1276
|View full text |Cite
|
Sign up to set email alerts
|

The first Δa observations of three globular clusters

Abstract: Globular clusters are main astrophysical laboratories to test and modify evolutionary models. Thought to be rather homogeneous in their local elemental distribution of members, results suggest a wide variety of chemical peculiarities. Besides different main sequences, believed to be caused by different helium abundances, peculiarities of blue horizontal-branch stars and on the red giant branch were found. This whole zoo of peculiar objects has to be explained in the context of stellar formation and evolution. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This is a very small percentage compared to the value of the Milky Way (up to 15%). However, an incidence that low in the LMC had already been discovered (Paunzen et al 2014), and supports the fossil theory as the origin of the stable stellar magnetic field; the global magnetic field of the SMC is much weaker than in the Milky Way. It is possible that the lower global metallicity also plays a role, though that has not yet been confirmed by theory.…”
Section: Results and Outlooksupporting
confidence: 74%
See 1 more Smart Citation
“…This is a very small percentage compared to the value of the Milky Way (up to 15%). However, an incidence that low in the LMC had already been discovered (Paunzen et al 2014), and supports the fossil theory as the origin of the stable stellar magnetic field; the global magnetic field of the SMC is much weaker than in the Milky Way. It is possible that the lower global metallicity also plays a role, though that has not yet been confirmed by theory.…”
Section: Results and Outlooksupporting
confidence: 74%
“…Since the 1970s CP and other non-standard stars in the Galactic field and in open clusters have been targets of photoelectric observations, and more latterly of CCD Δa photometry, leading to numerous publications. Observations have since been extended to globular clusters and to the Large Magellanic Cloud to search for all types of non-standard objects (Paunzen et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Although variability or binarity might interfere the results, the photometric system can be considered as an efficient pre-selection tool in particular for mCP stars. The system was not only applied to Galactic field stars, open clusters (Netopil et al 2007) and globular clusters (Paunzen et al 2014a), but also to clusters in the Large Magellanic Cloud (Paunzen et al 2006a), where photometric mCP star detections are also confirmed by spectroscopy (Paunzen et al 2011).…”
Section: Introductionmentioning
confidence: 99%